The Intersection of Financial Technology and Higher Education: Opportunities, Challenges, and Implications - -Puripunpinyoo, Anucha Wittayakorn (Electronic Journal of Business and Management, 2024)
This research paper explored the convergence of financial technology (fintech) and higher education, analyzing the opportunities, challenges, and implications of their integration. The paper examines how fintech innovations are reshaping the landscape of higher education, facilitating access, affordability, and efficiency for students at a private university in Bangkok, Thailand. The study population consisted of current students at the university who had experience with fintech services. The purposive sampling technique was applied, resulting in 25 respondents. Qualitative data were collected through in-depth interviews. Through a comprehensive review of the literature and case studies, the paper elucidates the key roles of fintech in areas such as digital payment solutions, personal finance management, investment platforms, and AI-powered adaptive learning. Moreover, the paper discusses the challenges and ethical considerations associated with using fintech in higher education, including privacy concerns, digital divide issues, and the need for regulatory frameworks. Finally, the paper provides insights into future trends and directions in this rapidly evolving field, highlighting the potential transformative impact of fintech on the future of education.